Optimization of culture conditions for antibacterial substance production from newly isolated Brevibacillus laterosporus EA62 - Demirkan, Elif; Aybey, Aynur; Usta, Alev (The European Research Journal, 2021)
Objectives: In the present study, it was reported the effects of some nutritional (amino acid, carbon, nitrogen and metal sources) and physical factors (pH and temperature) on antibacterial substance activity of Brevibacillus laterosporus EA62. Methods: The agar well diffusion assay was performed to evaluate the antibacterial activity of the substance. The antibacterial activity of the new substance was examined against four pathogenic bacteria under different nutritional and physical conditions. Results: The best antibacterial activity was obtained in modified medium consists of the 5% glucose, 0.1% tryptone, 0.05% MgSO4+CaCO3 and 0.5% glutamic acid. For physical parameters, maximal activity was observed after 72 h when incubated at 37°C, pH 7.0. Conclusions: This study indicates that Brevibacillus laterosporus EA62 could be an important source of antibacterial substances under this medium optimization.